HAKEKAT NILAI PERSATUAN DALAM KONTEKS INDONESIA (Sebuah Tinjauan Kontekstual Positif Sila Ketiga Pancasila) - Hanafi Hanafi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
This article described the existence of Pancasila as an ideology which has several impor- tant functions to regulate the life of the nation and state.Especially through the principles of Indone- sian unity. The method used is library research or library research. The results showed that Pancasila was an unifying national ideology that was right for the Indonesian nation, as a new instrument should be held in order to reactualize the values of Pancasila in Indonesian society. A great nation is a nation that is able to withstand its ideology by maintaining a unity in it as a whole. DOI: http://dx.doi.org/10.17977/um019v3i12018p056